Dance therapy combined with patient education improves quality of life of persons with obesity: A pilot feasibility study for a randomised controlled trial. Issue 1 (January 2017) - Allet, Lara; Müller-Pinget, Solange; Punt, Ilona; Edelsten, Charlotte; Ballif, Aurélie; Golay, Alain; Pataky, Zoltan
Highlights: Dance therapy combined with patient education improve quality of life of obese people. Mainly females adhere to dance therapy. Dance therapy is appreciated by patients. Dance therapy shows no added value compared to an educational program alone. Summary: Objective: To assess the effect of dance therapy combined with patient education on quality of life, functional capacity (lower limb power and endurance) and physical activity level in obese individuals. Methods: Thirty-three obese patients were randomised to a control group (structured patient education ambulatory program), and 34 to an intervention group (structured patient education ambulatory program combined with weekly sessions of dance therapy). Patients' quality of life, physical function and physical activity level were assessed at baseline and after 16 weeks. Results: Almost only women were willing to enrol in the study. Participants of the intervention group significantly improved their quality of life ( p = 0.023), and particularly self-esteem ( p = 0.014). However, dance therapy added to a patient educational program did not produce statistically significant higher effects than a patient education program alone on functional capacities and patients' physical activity level. Conclusion: A 16 week structured patient educational program combined with dance therapy seems to have a positive effect on the quality of life of obese people, but no effect on functional capacities and physical activity. Practice implication: Dance therapy combined with structured patient education is an interesting approach to improve quality of life of obese people.